The Role of HRM in Global Transition to Green Economy Sustainability in Indonesia's Halal Industry - Rahmat, Taufiq; Apriliani, Diah; Ardiansyah, Iwan; Bukhori, Reza Fauzi (Universitas Pendidikan Nasional, 2024)
Indonesia halal industry faces challenges in adopting sustainable practices within the green economy framework, primarily due to limited human resource readiness. This study examines the role of Green Human Resource Management (Green HRM) in strengthening the global competitiveness of halal SMEs engaged in international exports. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observations, and document analysis involving three business owners from the Halal Product Producers Association of Indonesia, representing western, central, and eastern regions. Findings indicate that Green HRM facilitates the development of green skills and sustainability-focused leadership, addressing gaps in awareness and capability among halal SMEs. Practical implications include integrating Green HRM into HR policies, emphasizing sustainability training and global green certifications. Additionally, the use of digital technology is highlighted as a means to expand access to training and accelerate the adoption of sustainable practices. The study's limitations include its focus on export-oriented halal SMEs, which may not fully represent the entire sector. Future research could explore the application of Green HRM in domestically focused halal businesses and assess long-term impacts on organizational performance. These findings underscore the need for global collaboration, government support, and human resource capacity-building to ensure the successful implementation of Green HRM in Indonesia’s halal industry